Effect of viral suppression on hepatic venous pressure gradient in hepatitis C with cirrhosis and portal hypertension. Issue 10 (10th April 2017) - Afdhal, N.; Everson, G. T.; Calleja, J. L.; McCaughan, G. W.; Bosch, J.; Brainard, D. M.; McHutchison, J. G.; De‐Oertel, S.; An, D.; Charlton, M.; Reddy, K. R.; Asselah, T.; et al.
Summary: Portal hypertension is a predictor of liver‐related clinical events and mortality in patients with hepatitis C and cirrhosis. The effect of interferon‐free hepatitis C treatment on portal pressure is unknown. Fifty patients with Child‐Pugh‐Turcotte (CPT) A and B cirrhosis and portal hypertension (hepatic venous pressure gradient [HVPG] >6 mm Hg) were randomized to receive 48 weeks of open‐label sofosbuvir plus ribavirin at Day 1 or after a 24‐week observation period. The primary endpoint was sustained virologic response 12 weeks after therapy (SVR12) in patients who received ≥1 dose of treatment. Secondary endpoints included changes in HVPG, laboratory parameters, and MELD and CPT scores. A subset of patients was followed 48 weeks posttreatment to determine late changes in HVPG. SVR12 occurred in 72% of patients (33/46). In the 37 patients with paired HVPG measurements at baseline and the end of treatment, mean HVPG decreased by ‐1.0 (SD 3.97) mm Hg. Nine patients (24%) had ≥20% decreases in HVPG during treatment. Among 39 patients with pretreatment HVPG ≥12 mm Hg, 27 (69%) achieved SVR12. Four of the 33 (12%) patients with baseline HVPG ≥12 mm Hg had HVPG <12 mm Hg at the end of treatment. Of nine patients with pretreatment HVPG ≥12 mm Hg who achieved SVR12 and completed 48 weeks of follow‐up, eight (89%) had a ≥20% reduction in HVPG, and three reduced their pressure to <12 mm Hg. Patients with chronic HCV and compensated or decompensated cirrhosis who achieve SVR can have clinically meaningful reductions in HVPG at long‐term follow‐up. (EudraCT 2012‐002457‐29).